Analysis of Genetic Diversity of Sago Population in Meranti Islands Based on Morphological Characteristics and Start Codon Targeted Polymorphism (SCoT) and matK Marker - Paramita, Pradnya; Deviona, Deviona; Herman, Herman (Jurnal Biologi Tropis, 2025)
Sago is an iconic agricultural commodity from the Meranti Islands region. Sago plantations cover 40,386 hectares. Diverse production yields and morphological differences in sago populations indicate high genetic diversity. This study aims to identify sago plants in the Meranti Islands and classify them based on similarities in morphological traits and DNA analysis. DNA analysis was carried out using SCoT and MatK markers. The research stages included sample collection, total DNA isolation, total DNA electrophoresis, total DNA amplification with SCoT and MatK primers, and data analysis. The results showed that based on morphological traits, sago populations in the Meranti Islands consist of three groups: BB, TB, and BJ. The dendrogram generated from the analysis of binary data SCoT using the UPGMA method and MatK analysis using BLAST in Genebank showed that these three groups are distinct and have different similarity coefficients. The BB group has a higher similarity coefficient with the BJ group compared to the TB group. There is no high genetic variation within these groups due to vegetative propagation of sago.